(untitled) (Academicia Globe: Inderscience Research, 2022)
In given article, the topical problems in the education of young people, such as self-knowledge, the formation of the phenomenon of human knowledge, the study of man as an external aesthet-ic, spiritual and aesthetic, moral and social value are considered.